β-Barrels and Amyloids: Structural Transitions, Biological Functions, and Pathogenesis - Anna I. Sulatskaya (MDPI AG, 2021)
Insoluble protein aggregates with fibrillar morphology called amyloids and β-barrel proteins both share a β-sheet-rich structure. Correctly folded β-barrel proteins can not only function in monomeric (dimeric) form, but also tend to interact with one another—followed, in several cases, by formation of higher order oligomers or even aggregates. In recent years, findings proving that β-barrel proteins can adopt cross-β amyloid folds have emerged. Different β-barrel proteins were shown to form amyloid fibrils in vitro. The formation of functional amyloids in vivo by β-barrel proteins for which the amyloid state is native was also discovered. In particular, several prokaryotic and eukaryotic proteins with β-barrel domains were demonstrated to form amyloids in vivo, where they participate in interspecies interactions and nutrient storage, respectively. According to recent observations, despite the variety of primary structures of amyloid-forming proteins, most of them can adopt a conformational state with the β-barrel topology. This state can be intermediate on the pathway of fibrillogenesis (“on-pathway state”), or can be formed as a result of an alternative assembly of partially unfolded monomers (“off-pathway state”). The β-barrel oligomers formed by amyloid proteins possess toxicity, and are likely to be involved in the development of amyloidoses, thus representing promising targets for potential therapy of these incurable diseases. Considering rapidly growing discoveries of the amyloid-forming β-barrels, we may suggest that their real number and diversity of functions are significantly higher than identified to date, and represent only “the tip of the iceberg”. Here, we summarize the data on the amyloid-forming β-barrel proteins, their physicochemical properties, and their biological functions, and discuss probable means and consequences of the amyloidogenesis of these proteins, along with structural relationships between these two widespread types of β-folds.